Application of Cation Resin Regeneration for Ferrous (Fe2+) and Manganese (Mn2+) Removal from Shallow Groundwater using Packed-Bed Column with Thomas Model. Issue 1 (1st December 2022) - Mangarengi, N A P; Abdullah, N O; Fisu, A F
Abstract: One of the factors influencing freshwater contamination is caused by pollutants and organic matter from anthropogenic activities. The appearance of ferrous and manganese metal ions in water systems, especially in shallow groundwater, has become a significant problem. When reacted in the air, an extreme amount of metal ferrous may cause turbidness and severe odor, particularly carrying a dark-brown color to fabrics. Water distribution can also easily be obstructed by iron bacteria in the pipes. It is similar to iron, and manganese has a detrimental effect on the natural environment, human hygiene, and sanitation. The higher influent ferrous and manganese concentration led to the adsorption process getting saturated quicker and a steeper breakthrough curve. The saturation time (ttotal) of the adsorption for ferrous concentration decreased from 430 minute (2 mg/l) to 420 minute (4 mg/l) to 380 minute (6 mg/l) with the elevation of Fe2+ influent concentration. In comparison, the saturation time for manganese concentration dropped from 463 minute (2 mg/l) to 460 minute (4 mg/l) to 420 minute (6 mg/l). Ferrous adsorption capacity (qeq) grew between 0.0046 mg/g and 0.0838 mg/g, followed by a growth in influent concentration. It is similar to manganese. The adsorption performace raised between 0.0216 mg/g and 0.109 mg/g. The Thomas model's R Square (R2) indicates a better fitting (0.788 – 0.8922) with field data.